Shielding parameters of leaded cement mortar - Abdel-Razek, Yassin A. (Universitas Sebelas Maret, 2023)
The Cathode ray tubes (CRTs) represent more than 70% of global e-waste sets. The glass of the CRT is doped with lead to prevent emission of radiations especially electrons. The glass at the panel and neck of the CRT along with the cement mortar, a mixture of 70% neck glass and 30% cement (mix70), are investigated mathematically as shielding materials from photons having energies in the range 0.06-3 (MeV). Experimentally the material mix70 is tested at energies 0.238 and 0.583 (MeV). Good agreement was recognized between the calculated shielding parameters and that obtained experimentally while complete equality between the calculated parameters carried out using the online XCom software or Phy-X software except at low energies for concrete material. Glass from panel, neck and mix70 have acceptable shielding characteristics at and below the energy 0.238 (MeV) or generally at the X-ray region. Neck glass has good shielding parameters at the chosen energy region and it is nominated as a shielding material for many nuclear applications. To enhance the shielding characteristics of the material mix70 it should be compacted during preparation to get higher density. The present work tested the shielding properties of leaded glass composites to find out its integrity for practical shielding applications and radiological safety.